Minimum wage in Bangladesh: Awareness and impact a case of leather sector - Khaleque, Md Abdul; Eusuf, Mohammad Abu (Asian Development Policy Review, 2024)
This paper aims to explore the awareness of the minimum wage among workers in the tannery sector and assess its impact on poverty. The national minimum wage is a policy instrument for protecting workers’ rights. It has an effect on the employment, inequality, equity, and poverty of the workers. The effect is assessed using descriptive and econometric tools and techniques. The regression analysis is used to find the key social and economic determinants of poverty, along with the components of the minimum wage. In total, 120 workers are randomly chosen for interviews. The study shows that workers are less aware of the minimum wage, and 89% report the non-availability of the minimum wage. Nearly 55% of the workers’ families live below the poverty line. The Probit model-based regression results show that the implementation of bonuses and annual increments according to the minimum wage policy reduces the odds of poverty significantly. The presence of workers’ unions has no effect on the eradication of poverty, but household characteristics, particularly household size, are found to be a key factor in poverty. Sector experts consider non-compliance a governance failure in the tannery sector and suggest awareness campaigns, a reduction of job informality, and sanctions as deterrents to non-compliance.